A way forward to European standard on Halal food - Kayadibi, Saim (Muhammadon Global Centre for Research and Development, 2014)
One of the fastest growing food industries is halal industry. It is therefore the halal food industry is a very crucial for Muslims around the world as it helps to ensure them that the food consumed is shari‘ah compliant. Although the halal food market currently is estimated at USD 632 billion per year, it will reach to USD 2.1 trillion. As the global Muslim population is increasing from 1.8 billion to more than 2 billion, the expectation of the halal food market will be increased. Therefore, demand of Muslims for good quality, clean, safe and genuine halal products is increased accordingly. In order to respond the demands of Muslim people, the halal food requirements must be standardized. Although there are many halal standard bodies in the world as well as in the European Union (EU), there is no consensus on a specific halal standard. Due to disunity, every country has its own certification body which brings to disagreements over slaughtering methods, packaging, animal feed, logistics etc. In order to solve this disunity, with initiative of the European Committee for Standardization (CEN) set up a Working Group to analyse the feasibility of a European Standard on halal food. Türkiye and Austria were allocated as twinning partners to create a new Project Committee for halal food standard. This paper aims to investigate the way forward to the creation of a new Halal Standard in the European Committee as one standard for all halal foods in the EU, which is recognised by all Muslims. Keywords: Halal Standard; European Union; Turkish Standards Institute; Austrian Standards Institute. JEL codes: O52; O53; O57; F13; F15; L11